Adaptation of the "active communication education" programme into Spanish for older adults with hearing loss. (1st September 2020) - Rivera, Sebastián; Marcotti, Anthony; Fuente, Adrian; Fuentes-López, Eduardo; Hickson, Louise
Abstract: Objective: To adapt the Active Communication Education (ACE) programme into Spanish. In addition, this study aimed at determining the effects of the adapted ACE programme on the social/emotional impacts of hearing loss and hearing functioning in a group of older adults with hearing loss who do not wear hearing aids. Design: This was an exploratory cohort study. Study group participants received the newly adapted ACE programme and control group participants received a cognitive stimulation programme. The Shortened Hearing Handicap Inventory for the Elderly in Spanish (HHIE-S) and the Spanish version of the Amsterdam Inventory for Auditory Disability and Handicap (S-AIADH) were carried out before and after each programme. Study sample: Sixty-six older adults with hearing loss and who did not wear hearing aids were randomly assigned to either an ACE group ( n  = 30) or a cognitive stimulation group ( n  = 36). Results: Participants who received the ACE programme showed a significantly larger improvement for the S-AIADH than did the cognitive stimulation group participants. Conclusions: The ACE programme has been adapted into Spanish for use with Chilean older adults with hearing loss. The results show that older adults report better functioning in listening situations after attending the sessions of the adapted ACE programme.